2021
DOI: 10.1177/1759720x211041854
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab in axial spondyloarthritis: a narrative review of clinical evidence

Abstract: Axial spondyloarthritis (axSpA) is a chronic inflammatory rheumatic disease characterized by inflammation and new bone formation in the axial skeleton. AxSpA is considered a spectrum of disease that includes two subtypes identified by the Assessment in SpondyloArthritis International Society classification criteria, namely, radiographic (r-axSpA usually referred to as ankylosing spondylitis) and non-radiographic axSpA (nr-axSpA). Although the burden of disease appears similar between the two classified subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Interleukin (IL)-17 is a key player in the pathogenesis of SpA [13][14][15][16] and a new class of biologics blocking IL-17 has been developed and approved for treatment as an alternative to TNFi [17,18]. In clinical trials, secukinumab, a fully human anti-IL17A IgG1/κ monoclonal antibody, has in fact shown good efficacy and safety in both AS and PsA [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL)-17 is a key player in the pathogenesis of SpA [13][14][15][16] and a new class of biologics blocking IL-17 has been developed and approved for treatment as an alternative to TNFi [17,18]. In clinical trials, secukinumab, a fully human anti-IL17A IgG1/κ monoclonal antibody, has in fact shown good efficacy and safety in both AS and PsA [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…26 Finally, post-hoc analysis of randomized trials confirmed the efficacy of secukinumab in AS patients over different domains including pain, fatigue, spinal stiffness, articular function, laboratory serum markers of inflammation, work productivity and health-related quality of life (reviewed in). 27 …”
Section: Anti-il-17 Drugsmentioning
confidence: 99%
“…[6] All these data obtained from RCT are useful in treatment decision making, but strict inclusion and exclusion criteria mean that trial populations may not be truly representative of patient populations in clinical practice. [3] Drug survival is a composite measure of effectiveness and safety. [6] With this in mind, we conducted a longitudinal observational retrospective study to ascertain survival rates of TNF-i & IL17-i therapies, as well as the reasons and potential predictors for drug discontinuation and switching between both groups in axSpA patients under routine clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, switching TNF-i therapy has become a common clinical practice and highlighted the need for new therapies with alternative mechanisms of action. [3] With more understanding of the pathophysiology of SpA & the introduction of IL-17 inhibitors (IL17-i) therapy, the management of such patients has witnessed a huge step forward. Interleukin (IL)-17A, a mediator in in ammatory pathways, has been identi ed as a key cytokine in the pathogenesis of axSpA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation